2008
DOI: 10.1037/a0013600
|View full text |Cite
|
Sign up to set email alerts
|

Relation of reward from food intake and anticipated food intake to obesity: A functional magnetic resonance imaging study.

Abstract: We tested the hypothesis that obese individuals experience greater reward from food consumption (consummatory food reward) and anticipated consumption (anticipatory food reward) than lean individuals using functional magnetic resonance imaging (fMRI) with 33 adolescent girls (M age = 15.7 SD = 0.9). Obese relative to lean adolescent girls showed greater activation bilaterally in the gustatory cortex (anterior and mid insula, frontal operculum) and in somatosensory regions (parietal operculum and Rolandic operc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

58
629
8
15

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 676 publications
(724 citation statements)
references
References 73 publications
58
629
8
15
Order By: Relevance
“…Several studies have evaluated neuronal responses to visual food cues at rest, showing changes in brain regions essential to the regulation of energy intake [48][49][50][51][52][53][54][55][56]. Killgore et al [51] observed significant activity in numerous food reward, inhibitory control, and visual brain regions (e.g., insula, amygdala, medial frontal gyrus, precuneus, etc.)…”
Section: Exercise and Neuronal Responsesmentioning
confidence: 99%
“…Several studies have evaluated neuronal responses to visual food cues at rest, showing changes in brain regions essential to the regulation of energy intake [48][49][50][51][52][53][54][55][56]. Killgore et al [51] observed significant activity in numerous food reward, inhibitory control, and visual brain regions (e.g., insula, amygdala, medial frontal gyrus, precuneus, etc.)…”
Section: Exercise and Neuronal Responsesmentioning
confidence: 99%
“…[14][15][16] Previous neuroimaging research in obese versus healthy-weight participants showed increased activity in several of these brain reward regions while viewing high-calorie versus neutral or low-calorie food pictures in a hungry state, 17 in a non-hungry state, 18,19 and in response to anticipated or actual consumption of a chocolate milkshake in a hungry state. 20 Most of these studies involved 'unbiased viewing', meaning that food pictures are shown without the instruction to imagine their taste.…”
Section: Introductionmentioning
confidence: 99%
“…A reduction in striatal dopamine-2 receptors was found in pathologically obese participants (Wang et al, 2001). This led to the hypothesis that obesity shares some neurobiological mechanisms with addiction disorders, for example, and mainly, the need to compensate for a decreased sensitivity of dopamine D2-regulated reward circuits by impulsive eating (Stice et al, 2008a(Stice et al, , 2008bWang et al, 2004). While this provides us with good evidence that the dopaminergic reward system is involved, it gives us no information about reward anticipation in MID paradigms.…”
Section: Obesity-related Changes In Striatal Reward Processingmentioning
confidence: 95%
“…In overweight adolescents, Stice and colleagues observed overactivation in the striatum as well as in OFC, insula, and opercular regions during anticipation of a food reward (Stice et al, 2008a(Stice et al, , 2008b. This altered response in individuals who were at risk for obesity was identified as an imaging biomarker for obesity risk.…”
Section: Obesity-related Changes In Striatal Reward Processingmentioning
confidence: 99%
See 1 more Smart Citation